2004
DOI: 10.3748/wjg.v10.i20.2944
|View full text |Cite
|
Sign up to set email alerts
|

Down-modulation of heat shock protein 70 and up-modulation of Caspase-3 during schisandrin B-induced apoptosis in human hepatoma SMMC-7721 cells

Abstract: Sch B is able to inhibit the proliferation of human hepatoma SMMC-7721 cells and induce apoptosis, which goes through Caspase-3-dependent and Caspase-9-independent pathway accompanied with the down-regulation of Hsp70 protein expression at an early event.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 41 publications
(34 reference statements)
1
25
0
Order By: Relevance
“…Three doses of Sch A and B (1, 10 and 20 mg/kg d) were chosen in this study, which were much lower than the most tolerated or toxic dosage (Hu et al, 2012a;Ko and Lam, 2002;Ko et al, 2008). It was reported that Sch B acts as a hormetic agent in cultured cells, with cytoprotective effects predominating at low concentrations and cytotoxicity occurring at high concentrations (Wu et al, 2004;Chiu et al, 2006). Therefore, to determine an appropriate dosage of Sch A and B for subsequent analysis, we preliminarily analyzed the samples by immunofluorescent staining in the SVZ, RMS and OB.…”
Section: Discussionmentioning
confidence: 99%
“…Three doses of Sch A and B (1, 10 and 20 mg/kg d) were chosen in this study, which were much lower than the most tolerated or toxic dosage (Hu et al, 2012a;Ko and Lam, 2002;Ko et al, 2008). It was reported that Sch B acts as a hormetic agent in cultured cells, with cytoprotective effects predominating at low concentrations and cytotoxicity occurring at high concentrations (Wu et al, 2004;Chiu et al, 2006). Therefore, to determine an appropriate dosage of Sch A and B for subsequent analysis, we preliminarily analyzed the samples by immunofluorescent staining in the SVZ, RMS and OB.…”
Section: Discussionmentioning
confidence: 99%
“…Schisandrin B induced apoptosis through caspase-3-dependent pathways accompanied with the down-regulation of heat shock protein 70 protein expression at an early event in human hepatoma SMMC-7721 cells (Wu et al, 2004). Schisandrin B can also substantially enhance caspase-9 accompanied with a significant elevation of mitochondrial breakdown in SMMC-7721 cells (Li et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the development of novel potent, but non-toxic anti-cancer reagents is worth a continuous effort. In the last decade, dibenzocyclooctadiene lignans (e.g., deoxyschisandrin, γ -schisandrin, schisandrin C, schisandrin, gomisin A, schisantherin A) (He et al, 1997) has attracted considerable attention as a potential anti-cancer drug or an adjuvant to the conventional therapeutic modalities for human hepatocellular cancer (Wu et al, 2004;Pan et al, 2006;Li et al, 2007). The present study was undertaken to assess the antitumor activity of schisandrin C against three established human cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, schisandrin B can inhibit the proliferation of human hepatoma SMMC-7721 cells and induce apoptosis, involving the caspase-3-dependent and caspase-9-independent pathways, accompanied by downregulation of Hsp70 protein expression at an early stage [2] . Schisandrin B enhances doxorubicin-induced apoptosis of SMMC7721 cells and MCF-7, a human breast cancer cell line, but not normal cells.…”
Section: Discussionmentioning
confidence: 99%